Feedback From Medical and Biology Students on Distance Learning: Focus on a Useful Interactive Software, Wooclap®. (December 2021) - Marin, Julie; Brichler, Ségolène; Lecuyer, Hervé; Carbonnelle, Etienne; Lescat, Mathilde
The coronavirus disease 2019 epidemic has prompted all universities to completely change their teaching in a very rapid way around the world. In France, most of the university courses for the year 2020 had to be delivered at distance. This can be an opportunity for some to rethink the place and the form of distance learning (DL). We present here the feedback of students about DL, who answered a questionnaire about classes they followed between October and December 2020. In addition, we evaluated the use and utility of an audience response system promoting interaction. Our results showed that overall the organization and internet connections allowed DL to run smoothly. Interestingly, all students were in favor of the development of a mixed solution, with distant lectures and face-to-face practical lessons. Finally, the use of interactive software such as Wooclap ® has proven to be easy to use and to develop for all lessons.